A comparative analysis between artificial intelligence and traditional learning methods in developing critical thinking skills among secondary education students in Peru - Castillo, Luis (2024)
Despite the fact that Artificial Intelligence (AI) holds the promise of improving education in Peru, its implementation presents challenges that must be approached with care to ensure ethical benefits. In the Peruvian context, AI is still in the process of adaptation, and its adoption could have negative effects on secondary education, as traditional methods foster critical thinking. A literature review supports the notion that AI may not adequately contribute to students' critical thinking. Emphasizing the importance of strengthening traditional educational methods that promote soft skills such as critical thinking, communication, and problem-solving among students.